2020
DOI: 10.1080/10548408.2020.1812469
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of willingness to pay a price premium for hotels’ water-saving initiatives

Abstract: This study examines customers' willingness to pay a premium to support hotels' water-saving initiatives and the effect of different explanatory variables: attitude toward water conservation, water problem awareness, willingness to sacrifice, reported water-saving behavior, and frugality. A Heckit model is applied to a sample of 681 tourists. Results show that 44.3% of tourists would pay a premium to stay in a hotel that had installed water-saving devices in rooms.The average price premium they would pay is 4.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 64 publications
1
27
0
1
Order By: Relevance
“…They further estimated that consumers expected a discount of $11 to accept the green practices related to water usage. On the other hand, Casado-Díaz et al (2020) found that consumers were willing to pay a premium of 4.69 Euros at hotels that had water-saving devices installed in the rooms. Similar results were also observed in the United States, where Kuminoff et al (2010) observed that hotels charge $9-$26 of premiums at green hotels.…”
Section: Green Initiativesmentioning
confidence: 99%
See 3 more Smart Citations
“…They further estimated that consumers expected a discount of $11 to accept the green practices related to water usage. On the other hand, Casado-Díaz et al (2020) found that consumers were willing to pay a premium of 4.69 Euros at hotels that had water-saving devices installed in the rooms. Similar results were also observed in the United States, where Kuminoff et al (2010) observed that hotels charge $9-$26 of premiums at green hotels.…”
Section: Green Initiativesmentioning
confidence: 99%
“…To address this, some recent studies have now started deconstructing the green hotel ‘black box’ to study the role of initiative‐specific attitudes. Attitude towards water conservation (Casado‐Díaz et al, 2020) and green purchase (L. Wang, Wong, & Narayanan, 2020) are two noteworthy ones to mention. However, these studies are relatively few and do not cover several other such green initiatives that exist.…”
Section: Thematic Focimentioning
confidence: 99%
See 2 more Smart Citations
“…Willingness to pay (WTP) is the amount that consumers think is most appropriate and are willing to pay for a product [17,18]. Casado-Díaz et al (2020) [19] pointed out in their study that 44.3% of travelers would pay extra to stay in hotels with water saving devices installed, with an average WTP of EUR 4. 29.…”
Section: Introductionmentioning
confidence: 99%